2007
DOI: 10.1007/s12011-007-8009-3
|View full text |Cite
|
Sign up to set email alerts
|

Selenium–Mercury Interactions in Man and Animals

Abstract: Selenium-mercury interactions were most extensively studied in relation to alleviation of Hg toxicity by added selenium. This presentation considers the influence of mercury on endogenous selenium, on its tissue and cellular "status" after lifelong or acute exposure to mercury vapor (Hg o). Discussed are data obtained from (1) humans living near or working in a mercury mine, and (2) rats experimentally exposed in the mine. Mercury vapor is unique--or similar to methylmercury--because of its ability to penetrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 31 publications
2
30
0
2
Order By: Relevance
“…Much of this elevation in Hg and Se persisted long after animals were switched from a high MeHg diet to a basal diet. Although the form of Hg was not determined, our results are consistent with deposition of a long-lived complex of Se with inorganic Hg rather than MeHg, based on the work of others where long-lived inorganic Hg accumulation was demonstrated in cats and primates, as well as humans [8,17,21,22]. The increase in Hg was accompanied by an increased level of Se, often in a Hg/Se molar ratio between 1 and 2.…”
Section: Discussionsupporting
confidence: 89%
“…Much of this elevation in Hg and Se persisted long after animals were switched from a high MeHg diet to a basal diet. Although the form of Hg was not determined, our results are consistent with deposition of a long-lived complex of Se with inorganic Hg rather than MeHg, based on the work of others where long-lived inorganic Hg accumulation was demonstrated in cats and primates, as well as humans [8,17,21,22]. The increase in Hg was accompanied by an increased level of Se, often in a Hg/Se molar ratio between 1 and 2.…”
Section: Discussionsupporting
confidence: 89%
“…This mechanism involves the reaction of mercury with selenium, which is an essential trace element [44,45]. The protective effects of selenium against mercury toxicity have been demonstrated in many animals and in humans [46,47]. Therefore, selenium concentration must also be considered when Hg concentration is high or above the limits.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the detection of the Se II -PC 2 complex and Se-cysteinylserine glutathione in Thunbergia alata suggested that symptoms of increased toxicity may have been due to the competition of Se II with As III for sulfhydryl groups, which are crucial to arsenite detoxification in plant cells [59]. A Zebrafish Se reduces visual deficits due to developmental Hg exposure [74] A Diatoms and mussels Se significantly inhibits the uptake of Hg [196] SeProt/ Hg 0 A Humans Se detoxifies Hg [197] SeProt/MeHg + A Human cells Hg induces a "selenium-deficient-like" condition [136] A Mice Hg affects the activities of selenoenzymes [71] Interactions of selenium-and sulfur-containing species Se species/S species A Bacterial systems Se appears to use the sulfur enzymatic system [79] A Se-hyperaccumulator plant Important differences between S and Se biochemistries [ A antagonism, S synergism, SeMet selenomethionine, SeProt selenoproteins, MeHg + methylmercury, SeBet selenobetaine, iAs(III) AsO 3 3− or AsO 2…”
Section: Protection Against Arsenic Toxicity By Seleniummentioning
confidence: 99%